Quality Assurance Concepts of Institutionalization: Some Indicators Towards Higher Educational Development Policy in Libya - Harathi, Milad El (Richtmann Publishing, 2012)
The aim of this paper is to lay down some indicators for establishing new Libyan national developmentpolicy in the higher education sector, after the political changes in Libya in 17-2-2011 uprising anddemolishing the old mechanism of controlling the higher education system in Libya. Its attempt shall bebased on rediscover ways of achieving quality and sustaining it in the Libyan higher education system. Thistherefore, is the task of this paper. It will examine the concept of quality assurance and apply it to a LibyanUniversity Institute.